2017
DOI: 10.31223/osf.io/8gsqw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential growth of deformation bands in carbonate grainstones in the hangingwall of an active growth fault: Implications for deformation mechanisms in different tectonic regimes

Abstract: a b s t r a c tDeformation bands in porous sandstones have been extensively studied for four decades, whereas comparatively less is known about deformation bands in porous carbonate rocks, particularly in extensional settings. Here, we investigate porous grainstones of the Globigerina Limestone Formation in Malta, which contain several types of deformation bands in the hangingwall of the Maghlaq Fault: (i) bed-parallel pure compaction bands (PCB); (ii) pressure solution-dominated compactive shear bands (SCSB) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…Rotevatn et al . [] in their recent work only found compaction bands in a rather limited area around an active fault and concluded that these structures could only grow in zones with different and specific host rock properties. Existing laboratory studies support this idea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotevatn et al . [] in their recent work only found compaction bands in a rather limited area around an active fault and concluded that these structures could only grow in zones with different and specific host rock properties. Existing laboratory studies support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…Both field [ Mollema and Antonellini , ; Schultz et al ., ; Eichhubl et al ., ], laboratory [ Baud et al ., ; Tembe et al ., ], and theoretical [ Wang et al ., ] studies suggest that compaction bands developed in relatively homogeneous high porosity (typically >20%) sandstone. Significantly less work was dedicated to the occurrence of compaction bands in limestone formations, even if several field examples were reported in Italy [ Tondi et al ., ; Rustichelli et al ., ] and more recently in Cyprus [ Rotevatn et al ., ]. Rotevatn et al .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of experimental studies have reported compaction localization in carbonates (Arroyo, Castellanza, & Nova, ; Baxevanis et al, ; Cilona et al, , ) but to date, the link between these results and the field examples (Tondi et al, ; Rustichelli et al, ; Rotevatn et al, ) remains unclear. Our new AE location data on SML show without ambiguity that compaction localization occurred in this rock.…”
Section: Discussionmentioning
confidence: 99%
“…Cataclasis in carbonate rocks is commonly accompanied by grain boundary pressure solution, documented at a variety of burial depths (e.g. Cilona et al, 2012;Viti et al, 2014;Rotevatn et al, 2016). Additionally, the presence of phyllosilicate material within the faulted stratigraphy have been shown to produce alternative fault rock textures to those observed in Malta.…”
Section: Comparisons With Other Fault Zonesmentioning
confidence: 99%
“…However, the lithofacies juxtaposition is the same as for the VLF; a GL hanging wall juxtaposed against an Xlendi footwall. The lack of a distributed damage zone may be due to strain accommodation via the formation of an intense array of deformation bands in the hanging wall, as described byRotevatn et al (2016), combined with the junction with a series of conjugate slip surfaces that are parallel to the principal orientations of this deformation band array. Due to there being no distributed damage zone, cataclasite at the 50 m displacement fault zone is more continuous than for the m and 90 m displacement fault zones (FRC = 0.8, 0.15, and 0.47 respectively).…”
mentioning
confidence: 99%